Efektivitas Penggunaan Instagram Sebagai Media Promosi Di Desa Tangkit Baru Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Rahnia; Sissah; Lidya Anggraeni (JOURNAL SAINS STUDENT RESEARCH, 2023)
Since sharia-based marketing is one of the marketing methods based on the Quranand the Prophet SAW's Sunnah, it occupies a strategic position since it is marketing that is not just profit-oriented but also contains worship values. The following are the issues with this study, according to the author: Instagram @agrowisata_nanas can aid all business operations, starting from online promotion and marketing, inorder to enhance household income in Tangkit Baru Village. Instagram@agrowisata_nanas can promote products made by people of Tangkit BaruVillage. The goal of this study is to determine the impact of using Instagram@agrowisata_nanas on the local economy in Tangkit Baru Village, Sungai GelamDistrict, Muaro Jambi Regency and to determine the effectiveness of sharia-basedmarketing on Instagram @agrowisata_nanas in promoting local resident’sproducts. In qualitative research, sample selection is done both before and duringthe study process (Emergent Sampling Design). The idea is that the researcherselects a certain subject who is thought to supply the data required, and then theresearcher can identify additional samples under consideration will provide morecomplete data based on the data or information gained from the previous sample.The term "Serial Selection of Sample Units" refers to this procedure. Five business actors and Hendra Kurniawan, the administrator of the Instagramaccount @agrowisata_nanas, will serve as the research's informants. The@agrowisata_nanas admin promotes the products of these five individuals on theaccount. This study used a qualitative methodology. Using Nuruh Huda's (2017)theory of product, price, communication, community, and distribution as well asthe AIDA model using Ramadan and Fatchiya's (2021) theory of attention, interest, desire, and action, the results demonstrated the efficacy of using Instagram as apromotional medium in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency.